Retrospect and Outlook of Research on Regional Haze Pollution in China: A Systematic Literature Review - Li Li (MDPI AG, 2021)
Regional haze pollution, a severe atmospheric environmental problem, has profoundly harmful effects on the ecological environment, public health and the quality of economic development, and has accordingly attracted considerable attention from policymakers, researchers and the public. This article comprises a systematic literature review of the existing research on the theoretical mechanism, empirical analysis and institutional arrangement of regional haze pollution. As a result, it is found that various studies from multiple disciplines have touched upon the relevance of haze issues, including theoretical and experimental research on its formation, evolution and mechanisms from the perspective of the natural sciences, as well as empirical analysis and policy research on governance strategies, effects and mechanisms from the perspective of the social sciences, yet a systematic review and critical assessment synthesizing the above research is urgently needed. Future directions and research prospects are highlighted, showing that it is necessary to supplement and improve the theory and practice concerning the identification, measurement and assessment of haze pollution, as well as regional controlling strategies and policy implementation assessments. In short, in this review, we have aimed to help integrate the theoretical and empirical consensus in multidisciplinary fields, thereby promoting the accurate analysis, fine management and the development of precise policies in regards to regional haze pollution.